Dementia: Risk Factors and Updated Review - Nepal, H; Jeffrey, B; Bhattarai, M (Journal of Psychiatrists’ Association of Nepal, 2018)
With the tremendous rise in the aging population around the world, the prevalence of Major Neurocognitive Disorders is skyrocketing. In the same manner, the burden of the morbidity and mortality associated with the such disorders has been a global health problem. Most of the time, the cause of Major Neurocognitive Disorder is unknown. Our review article is an attempt to summarize the likely modifiable risk factors associated with the disorder. In this manner there could be insight into further confirmatory and exploratory evidence based studies of these factors for early intervention to prevent and delay the progression of full blown disease. Among the modifiable risk factors, the ones that have been discussed here are smoking, activity both physical and cognitive, cardiovascular risk factors, depression, traumatic brain injury and sleep. J Psychiatrists’ Association of Nepal Vol. 6, No. 2, 2017, Page: 3-7